Genome-wide characterization of chalcone synthase genes in sweet cherry and functional characterization of CpCHS1 under drought stress - Hou, Qiandong; Li, Shuang; Shang, Chunqiong; Wen, Zhuang; Cai, Xiaowei; Hong, Yi; Qiao, Guang (Frontiers in Plant Science, 2022)
Cherries are one of the important fruit trees. The growth of cherry is greatly affected by abiotic stresses such as drought, which hinders its development. Chalcone synthase (CHS, EC 2.3.1.74) is a crucial rate-limiting enzyme in the flavonoid biosynthetic pathway that plays an important role in regulating plant growth, development, and abiotic stress tolerance. In the current study, three genes encoding chalcone synthase were identified in the genome of sweet cherry (Prunus avium L.). The three genes contained fewer introns and showed high homology with CHS genes of other Rosaceae members. All members are predicted to localize in the cytoplasm. The conserved catalytic sites may be located at the Cys163, Phe214, His302, and Asn335 residues. These genes were differentially expressed during flower bud dormancy and fruit development. The total flavonoid content of Chinese cherry (Cerasus pseudocerasus Lindl.) was highest in the leaves and slightly higher in the pulp than in the peel. No significant difference in total flavonoid content was detected between aborted kernels and normally developing kernels. Overexpression of Chinese cherry CpCHS1 in tobacco improved the germination frequency of tobacco seeds under drought stress, and the fresh weight of transgenic seedlings under drought stress was higher than that of the wild type, and the contents of SOD, POD, CAT, and Pro in OE lines were significantly increased and higher than WT under drought stress. These results indicate cherry CHS genes are conserved and functionally diverse and will assist in elucidating the functions of flavonoid synthesis pathways in cherry and other Rosaceae species under drought stress.